The Practice of Community-Based Forest Management in Northwest Ethiopia - Tesfaye Mengie; László Szemethy (Land, 2025)
Community-Based Forest Management (CBFM) efforts are critical for sustainable natural resource governance in Northwest Ethiopia. This study investigated the various aspects of CBFM, emphasizing practical implementation in the context of the Awi Administrative Zone, Northwest Ethiopia. A structured questionnaire was handed out to 412 farmers across three districts—Dangila, Fagita Lokoma, and Banja. The quantitative data was analyzed using the Likert scale with SPSS version 23 software. Findings indicate that insufficient financial support (44%), limited community participation (30%), and weak institutional arrangements (19%) are the major factors impeding effective CBFM, with statistically significant regional variation (χ2 = 242.8, df = 3, p = 0.000). On the other side, increased awareness and international support (34%) and enhanced local participation (36%) were the leading facilitators (χ2 = 512.05, df = 11, p = 0.000). We look at the practical aspects of CBFM, from community-led conservation efforts to sustainable harvesting techniques, emphasizing the importance of indigenous knowledge alongside modern methodologies. The CBFM project in the northwest part of Ethiopia have facilitated biodiversity protection and environmental resilience by integrating local perspectives with broader developmental goals. However, obstacles such as land tenure, resource conflicts, and capacity restrictions continue, requiring adaptive methods and legislative reforms. This paper contributes to the ongoing discussion on sustainable natural resource management by offering empirical insights into the dynamics of CBFM in the Awi administrative zone of northwest Ethiopia.